Clinical and laboratory characteristics of infants born to substance addicted mothers: a single center experience - Elbayiyev, Sarkhan; Çakır, Ufuk (Journal of Dependence, 2023)
Objective: It is known that the use of alcohol, illicit drugs and psychoactive substances during pregnancy is significantly associated with maternal, fetal and neonatal morbidities. We planned to investigate the characteristics of babies born to mothers who use illicit substances.Method: Babies born to mothers using illicit drugs and healthy babies born between September 2019 and December 2021 were included in the study. Demographic, clinical and laboratory data of the patients and modified Finnegan scores were recorded retrospectively from the file data.Results: A total of 24 infants, 11 infants of drug-using mothers and 13 healthy infants in the control group, were included in the study. Ages of mothers, gestational weeks, birth weights, and APGAR scores at 1st and 5th minutes of babies born to mothers who used substance were found to be statistically lower than healthy babies. The rates of leukopenia and neutropenia were found to be significantly higher in patients with a modified Finnegan score ≥8 and in need of morphine (n:4/11) compared to patients without morphine need (n:7/11).Conclusion: There is a need for detailed studies on the prevention of illicit substance use as a current health problem, the development of policies on early detection and follow-up, and the search for new biomarkers for the early detection of infants followed for neonatal withdrawal syndrome.
Keywords: Neonatal abstinence syndrome; pregnancy; newborn